2010
DOI: 10.1007/s11071-010-9655-0
|View full text |Cite
|
Sign up to set email alerts
|

Stationary solutions of a small gyrostat in the Newtonian field of two bodies with equal masses

Abstract: To cite this version:Tilemahos J. Kalvouridis. Stationary solutions of a small gyrostat in the Newtonian field of two bodies with equal masses. Nonlinear Dynamics, Springer Verlag Abstract The paper deals with the dynamics of a small gyrostat satellite acted upon by the Newtonian forces of two big bodies of equal masses which rotate around their center of mass. The gyrostat's equations of motion are derived and classes of its stationary solutions, as well as their stability are studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A further step in the complexity of the problem, and in the approximation to a real one, is to consider the motion of a gyrostat under the attraction of a Newtonian field. For this problem, some authors have found approximated analytical solutions for particular cases [7,32] and other authors have studied the equilibria and their stability when the gyrostat is in circular orbit [33,34] or in the gravity field of a number of di↵erent rigid bodies [21,35]. In this paper we focus on the stability of permanent rotations of a heavy gyrostat with a fixed point, that is to say when the gyrostat is under a uniform gravity field.…”
Section: Introductionmentioning
confidence: 99%
“…A further step in the complexity of the problem, and in the approximation to a real one, is to consider the motion of a gyrostat under the attraction of a Newtonian field. For this problem, some authors have found approximated analytical solutions for particular cases [7,32] and other authors have studied the equilibria and their stability when the gyrostat is in circular orbit [33,34] or in the gravity field of a number of di↵erent rigid bodies [21,35]. In this paper we focus on the stability of permanent rotations of a heavy gyrostat with a fixed point, that is to say when the gyrostat is under a uniform gravity field.…”
Section: Introductionmentioning
confidence: 99%
“…The gyroscope has attributes of great utility to navigational and aeronautical engineering, biology, optics, etc. [3][4][5][6][7][8]. Different types of gyroscopes (with linear or nonlinear damping, fluid, etc.)…”
Section: Introductionmentioning
confidence: 99%